2017
DOI: 10.18632/oncotarget.18013
|View full text |Cite
|
Sign up to set email alerts
|

PARP1expression and its correlation with survival is tumour molecular subtype dependent in glioblastoma

Abstract: Overexpression of PARP1 exists in various cancers, including glioblastoma (GBM). Although PARP1 inhibition is a promising therapeutic target, no comprehensive study has addressed PARP1's expression characteristics and prognostic role regarding molecular heterogeneity in astrocytomas including GBM. Our aim was to evaluate PARP1's associations with survival, WHO grade, lineage specific markers, and GBM transcriptomic subtypes. We collected genomic and clinical data from the latest glioma datasets of The Cancer G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…2 ). This finding is consistent with studies in pediatric diffuse intrinsic pontine glioma [ 41 ] and adult glioblastoma [ 42 ], both of which found enhanced PARP1 expression in clinical samples of human brain tumors.…”
Section: Discussionsupporting
confidence: 92%
“…2 ). This finding is consistent with studies in pediatric diffuse intrinsic pontine glioma [ 41 ] and adult glioblastoma [ 42 ], both of which found enhanced PARP1 expression in clinical samples of human brain tumors.…”
Section: Discussionsupporting
confidence: 92%
“…PARP1 is ultimately essential for DNA repair during TMZ-based treatment and radiation therapy (Figure 3) (83). PARP1 expression is associated with TP53 and ataxia telangiectasia—Rad3 related kinase (ATR) mutations (84). GSCs display elevated basal levels of activated ATR and CHK1 along with increased replication stress (RS) expression markers including foci marked with the single-stranded DNA binding protein, replication protein A, DNA damage markers γH2AX and 53BP1 (82).…”
Section: Replication Stress: Role Of Parp Proteins In Glioma Progressionmentioning
confidence: 99%
“…PARP-1 expression was reported in the nucleoli of neurons, oligodentritic cells, and astrocytes as well as the Purkinje cell layer in the cerebellum and the dentate gyrus (10). Nevertheless, it has been shown that malignant glial growths have elevated PARP-1 expression compared with healthy pediatric and adult brain tissue (11), forming an ideal foundation for CED-based therapeutics. Similarly important, PARP inhibitors not only quickly distribute and bind within PARP-expressing cells, but also simultaneously washout effectively from healthy tissues, resulting in high target-to-background contrast (10,12), potentially providing a large treatment window for CED therapy (7).…”
mentioning
confidence: 99%